STUDY OF C-PHYCOCYANIN FROM SPIRULINA PLATENSIS (GOMONT) GEITLER AS A SUBSTRATE CANDIDATE FOR PROTEASE ACTIVITY ASSAY OF PANCREATIN - Tursino
Pancreatin is a substance that contains several digestive enzymes, especially amylase, lipase and protease, obtained from the pancreas of mammals such as cattle and pigs. In the pharmaceutical field, pancreatin is used as an oral agent for pancreatic enzyme-replacement therapy (PERT) for patients with pancreatic exocrine insufficiency (PEI). In FI ed VI 2020, the pacreatin used was derived from the pancreas of Bos taurus bulls Pancreatin must meet the requirement for quality parameters. One of the quality parameters is related to pancreatin protease activity. In FI ed VI 2020, the substrate used in determining the activity of the protease enzyme is casein. However, in practice the use of casein has weaknesses such as solubility, preparation process, multi-stage analysis process and time consuming process. Several substrates have been used to replace casein such as azocasein, gelatin and hemoglobin. In this study, the candidate substrate used was C-Phycocyanin (CPC) from Spirulina platensis. This research was aimed to isolate, characterize, study the interaction of CPC with pancreatin, study of enzyme kinetics and application of CPC as a substrate in determining pancreatin protease activity. The research included isolation, purification and characterization of CPC, interaction of CPC with pancreatin, determining the relationship between the initial reaction rate and protease activity, protease kinetics assay and method validation. Isolation was carried out using a combination of homogenization method with mortar and pestle, sonication at 40% amplitude for 5 minutes, centrifugation at 2500 rcf for 15 minutes and filtration using filter paper. The resulting CPC was then purified by the aqueous two-phase system (ATPS) method with the PEG 6000 system 10 %w/v/ 1 M potassium phosphate buffer, pH 7.2 and dialysis with a cellulose membrane with a cut off of cut off 12 kDa - 14 kDa. The isolated solution was characterized by protein level, CPC level and purity at wavelengths of 620 nm and 652 nm, UV-Vis spectrum, excitation spectrum and emission spectrum. The kinetics assay was carried out by determining the relationship between the initial reaction rate and protease activity, maximum velocity (Vmax) and Km according to the Michaelis Menten and Lineweaver-Burk equations. Method validation includes accuracy, precision, linearity, limit of detection, and limit of quantitation. Isolation obtained two fractions namely FATPS-ND and FATPS-D fraction with protein level, CPC level and CPC purity of 63.7 ± 1.31 mg/100 mL, 12.6 ± 0.13 mg/100 mL, respectively, and 0.51 ± 0.002 (FATPS-ND); 33.3 ± 0.60 mg/100 mL, 9.4 ± 0.13 mg/100 mL and 0.85 ± 0.002 (FATPS-D). The results of UV-Vis spectra characterization showed that excitation and emission spectra of the two fractions were max at 620 nm, max excitation at 620 nm and max emission at 647 nm. The results of the interaction of CPC with pancreatin showed a reduction in the concentration of CPC in the time used. The relationship between initial reaction rate (Vo) and protease activity (5–30 IU/mL) showed a linear curve, especially at incubation time of 5 -30 minutes with R2 > 0.9. The enzyme kinetics study showed that the Vmax values for the reaction incubation time of 10, 20, 30 minutes were 2.59; 1.47; 1.31 µg/mL/min, respectively and Km values for same incubation time were 91.66; 70.86; 79.22 µg/mL, respectively. The values of these parameters are used to predict the Michaelis-Menten hyperbolic curve. The results of the specificity and selectivity test using FATPS-D showed that the matrix did not interfere with the determination of protease activity. This can be seen from the degree of deviation (% bias) which is still below 5% and the accuracy of the method is close to 100%. The results of the linearity test in the protease activity in a range of 30-80 IU/mL for both fractions showed a linear relationship between Vo and protease activity, which was indicated by the R2 value>0.99. In addition, the results of the calculation of the coefficient of variation of the fungi (Vx0) showed their respective values of 3.57% for FATPS-D and 3.01% for FATPS-ND. While the limit of detection and limit of quantization of the method were 4.99 and 16.64 IU/mL for FATPS-ND, respectively; and 5.93 and 19.76 IU/mL for FATPS-D. The results of the method accuracy showed that the percent recovery at the pancreatin level of 80, 100 and 120 %, respectively, was 113.4 ± 4.62; 108.5 ± 8.48 and 111.0 ± 6.38% for FATPS-ND; and 104.1 ± 2.15; 99.9 ± 3.94 and 101.3 ± 3.37% for FATPS-D. The results of the precision of the method on the first and second days showed coefficient of variation (CV) of 7.8% and 3.8% for FATPS-ND and 3.9% and 3.3% for FATPS-D. The application of the method on commercial samples showed protease activity of 17044.3 ± 472.25 IU/caplet for FATPS-D and 19587.7 ± 288.65 IU/caplet for FATPS-ND. In conclusion, CPC can be used as a new substrate candidate for the determination of pancreatin protease activity with the advantages of a simpler one step procedure and fewer reagents, therefore the analysis time is faster.